Transport properties of a weak topological insulator - Bi14Rh3I9 - Krishna, Nadella Vasanth (2018)
Topological insulators are a new phase of matter in condensed matter physics that fundamentally differs from conventional insulators and metals, in mixing both insulating and conducting properties. Their surface states, the existence of which is protected by topology of the band structure, are conducting whereas bulk shows conventional insulating or semiconducting properties. 2D topological insulators was recently theoretically predicted in 2006 [1] and experimentally evidenced in the year after [2]. The discovery of 3D TIs followed in 2008 [3]. Intense efforts have been done to understand the properties of this new topological phase. Although many experiments investigating the surface state properties were done by surface sensitive techniques like Angle Resolved Photo Emission Spectroscopy (ARPES) and Scanning Tunneling Microscope (STM) measurements, only little is known about their transport properties so far. 3D topological insulators are commonly known and mainly classified into strong and weak topological insulators depending on the nature of topological protection of their surface states [4]. The first weak topological insulator Bi14Rh3I9 was recently synthesized in TU Dresden [5]. ARPES and STM studies conducted on this material reveals the presence of 1D edge states on one facet as expected by theory so far, but transport properties of this material remains to be done. The aim of this thesis is to explore the transport properties of this material at low temperature (down to 4K), under magnetic field and in nanostructures of Bi14Rh3I9 (hall-bar like geometry). Apart from extracting some fundamental transport parameters like the electronic density and mobility, we will search for signature of transport along topological 1D edge channels.